Linear and Nonlinear Simulation for Quadrotor Dynamics Encompassing Induced Disturbance - Rizki Zuhri, Muhammad; Sidqi Islami, Zaim; Asti Rosalia, Citra (Jurnal Jaring SainTek, 2024)
Quadrotor is a rotorcraft that has four rotors, usually symmetrical and arranged in some specific configuration, i.e. ‘plus’ and ‘cross’ configuration. To test a new control system for quadrotor, it is necessary to put it on board first and have a flight test. However, controlling a quadrotor is a hard task, hence the risk of crash is high. This risk can be reduced by creating a simulation model that represents the dynamics of quadrotor accurately. This paper aims to provide the simulation model of a quadrotor. To increase accuracy of this model, the disturbance induced by the motion of the quadrotor were also taken int account. The simulation was built in Simulink based on the kinematics and dynamics equation of quadrotor both in linear and nonlinear simulation. In most cases, the attitude response (roll, pitch, and yaw) for both simulations were nearly the same. The most notable difference was for the elevation response in which the linear simulation tended to be unable to capture the deviation, while the nonlinear simulation was able to.